Future wind speed and energy potential in Togo for the period 2021-2040: Projections from CORDEX-Africa models - Lamboni Batablinlè; Kassiki Yessou-Gnouyarou; Lawson Latévi; Kpengou Lorimpo; Serge Bazyomo; Tchedre Kpéli Esso-ehanam; M. Djibibe Moussa Zakari; Magolmeena Bannaa; Lawin Agnidé Emmanuel (Center of Biomass & Renewable Energy (CBIORE), 2026)
This study assesses the wind energy potential across Togo by analyzing historical (2001–2020) and future (2021–2040) wind regimes using MERRA-2 reanalysis data and six bias-corrected CORDEX-Africa regional climate models (MIROC, MPI, ICHEC, NOAA, NCC, and IPSL). A Python-based analytical framework was developed to automate data compilation, visualization, and multi-model statistical processing, ensuring reproducibility and computational efficiency. Model performance was evaluated against ground-based observations using a multi-metric validation approach combining R², NSE, and RMSE. Results identify MERRA-2 (R² = 0.96, NSE = 0.95, RMSE = 0.35) and the RCMs MIROC, MPI, and ICHEC (R²=0.93–0.95, NSE=0.92–0.94, RMSE<0.45) as the most reliable sources for future wind projections. Seasonal and spatial analyses reveal pronounced heterogeneity across the country. During the rainy season, wind speeds in northern Togo reach 3.8–4.3 m/s, while the southern coastal zone maintains stable year-round winds ranging from 3.9 to 4.5 m/s due to the influence of persistent sea breezes. Future projections for 2021–2040 show an increase in wind speeds of 4–8 %, corresponding to wind power density enhancements of 9–30 %. Peak power density values are projected to reach approximately 52 W/m² in the north, 47 W/m² in the center, and 49 W/m² along the coast. Overall, these findings provide a robust scientific basis for region-specific energy strategies, including the development of hybrid wind–solar systems, targeted coastal installations, and optimized siting of northern wind farms. The results further highlight the potential of wind energy to support national electrification efforts and emerging green hydrogen initiatives, contributing to sustainable development and energy security in Togo.